2004
DOI: 10.1002/elps.200305852
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis combined with microdialysis in the human spinal cord: A new tool for monitoring rapid peroperative changes in amino acid neurotransmitters within the dorsal horn

Abstract: A method originally developed for the separation of the three neurotransmitters gamma-aminobutyric acid (GABA), glutamate (Glu) and L-aspartate (L-Asp) in microdialysis samples from rat brain (Sauvinet et al., Electrophoresis 2003, 24, 3187-3196) was applied to human spinal dialysates obtained during peroperative microdialysis from patients undergoing surgery against chronic pain. Molecules were tagged on their primary amine function with the fluorogene agent, naphthalene-2,3-dicarboxaldehyde (NDA), and, after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
(15 reference statements)
2
16
0
Order By: Relevance
“…In a series of interesting papers [101][102][103], Sauvinet et al [101] have shown the applicability of MEKC for the simultaneous analysis of GABA, Glu, and L-Asp in submicroliter samples of dialysates from rat striatum [101]. They developed this method using a commercially available instrument and validated the procedure on both analytical and pharmacological basis.…”
Section: Amino Acids In Microdialysatesmentioning
confidence: 97%
See 1 more Smart Citation
“…In a series of interesting papers [101][102][103], Sauvinet et al [101] have shown the applicability of MEKC for the simultaneous analysis of GABA, Glu, and L-Asp in submicroliter samples of dialysates from rat striatum [101]. They developed this method using a commercially available instrument and validated the procedure on both analytical and pharmacological basis.…”
Section: Amino Acids In Microdialysatesmentioning
confidence: 97%
“…They developed this method using a commercially available instrument and validated the procedure on both analytical and pharmacological basis. In addition, they also performed the simultaneous analysis of an antiepilectic drug (vigabratin) and the above amino acids in rat brain microdialysates [102] and determined these amino acids in human spinal dialysates obtained during peroperative microdialysis from patients undergoing surgery against chronic pain [103]. They used 75 mM sodium borate buffer, pH 9.2, containing variable concentrations of SDS (from 60 to 70 mM) and variable concentrations (from 5 to 10 mM) of hydroxypropyl-b-CD as BGE.…”
Section: Amino Acids In Microdialysatesmentioning
confidence: 99%
“…and 17 nM for GABA, Glu, and L-Asp, respectively [57]. This method allows an accurate measurement of the three amino acid neurotransmitters during an in vivo monitoring performed as rapidly as one sample per minute in the human spinal dorsal horn.…”
Section: Neurochemical Applications Of Cementioning
confidence: 98%
“…Typical electropherograms using CE-LIF of a microdialysate obtained from the spinal dorsal horn in a patient with chronic pain (top), a standard solution (middle) containing 500 nM GABA, 5 mM Glu/L-Asp compared to a brain dialysate obtained from rat striatum (bottom). Cysteic acid is the internal standard ( [57] with permission).…”
Section: Neurochemical Applications Of Cementioning
confidence: 99%
“…Analytical parameters quantified in both of these reports would be sufficient to identify key organic components of the L-arginine/NO pathway. Example of microdialysis systems that can be used in combination with CE-LIF for analysis of human cerebrospinal fluid samples with 1-min sampling have been recently described by Parrot et al [396].…”
Section: Microdialysis and Push-pull Sampling Hpce Of No Metabolitesmentioning
confidence: 99%